2011
DOI: 10.1111/j.1751-7133.2011.00266.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Protein Phosphorylation as a Regulatory Modality: Implications for Mitochondrial Dysfunction in Heart Failure

Abstract: Phosphorylation of mitochondrial proteins has been recognized for decades, and the regulation of pyruvate- and branched-chain α-ketoacid dehydrogenases by an atypical kinase/phosphatase cascade is well established. More recently, the development of new mass spectrometry-based technologies has led to the discovery of many novel phosphorylation sites on a variety of mitochondrial targets. The evidence suggests that the major classes of kinase and several phosphatases may be present at the mitochondrial outer mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 186 publications
(217 reference statements)
2
34
0
Order By: Relevance
“…Mitochondrial protein phosphorylation is an important mechanism for the modulation of mitochondrial function (Acin-Perez et al, 2009; O’Rourke et al, 2011). Previous reports including immunoelectron microscopy studies have shown that Src is located inside mitochondria, and Src activity is also important for the regulation of mitochondrial functions and cell viability (Hebert-Chatelain, 2013; Miyazaki et al, 2003; Salvi et al, 2002; Tibaldi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial protein phosphorylation is an important mechanism for the modulation of mitochondrial function (Acin-Perez et al, 2009; O’Rourke et al, 2011). Previous reports including immunoelectron microscopy studies have shown that Src is located inside mitochondria, and Src activity is also important for the regulation of mitochondrial functions and cell viability (Hebert-Chatelain, 2013; Miyazaki et al, 2003; Salvi et al, 2002; Tibaldi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a functional independent cAMP pathway in the mitochondrial matrix is very appealing, and is supported by the presence of sAC in this compartment; however, there are several debated points in this model. For instance, although there are reports suggesting the presence of PKA in the matrix [24,26], there is no evidence of a possible import mechanism for this enzyme [32]. The AKAPs could provide an alternative mechanism for targeting PKA in the matrix; however, to date, no AKAP has been identified in this compartment [18,26].…”
Section: Mitochondrial Matrixmentioning
confidence: 97%
“…In excitable cells such as cardiomyocytes, Mfn2 tethers mitochondria to the sarcoplasmic reticulum (30), the microdomain where Ca 2+ -induced Ca 2+ release is localized. Additional mechanisms for Ca 2+ -mediated alterations in mitochondrial structure and function include through PKA-AKAP, Ca 2+ -induced post-translational modifications and the mitochondrial Ca 2+ uniporter (MCU) (113, 114, 117, 118) (see below).…”
Section: Post-translational Modification (Ptm) Of the Mitochondrmentioning
confidence: 99%
“…multiple-reaction monitoring (133135), have identified >200 different phospho-transitions of proteins in the TCA cycle, and pyruvate dehydrogenase and branched-chain α-keto acid dehydrogenase complexes (118, 133, 135138). Bioinformatic site analysis suggests the involvement of PKA, PKC, casein kinase II, DNA-dependent kinase, tyrosine kinase, Src kinase, GSK-3, ERK1/2, and EGFR (118). Several of these kinases and phosphatases are either tethered to or are translocated to the OMM where they target membrane proteins such as Bcl-2, BAD, VDACs 1–3 and TOM70 (118).…”
Section: Post-translational Modification (Ptm) Of the Mitochondrmentioning
confidence: 99%